Pengabdian Budidaya Garam Dan Dampak Dari Peluasan Wilayah Tambak Garam Beserta Penanaman Pohon Di Desa Galis Kec. Gili Genting - Ali Armadi; Muhammad Misbahudholam AR; Abdullah hasan AS; Ahmad Shahibul Wafa; Moh. Yasir; Moh. Khairul Fattah; Fadila Fadila (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Salt is an important staple both in the body and as an ecosystem. The same as reforestation is done in order to protect the environment and can prevent the negative impact of salt cultivation which results in changes in weather that is very hot than usual, community service carried out by KKN (Real Work Lectures). ) from STKIP PGRI Sumenep for the 2023/2024 academic year which is placed in the village of Galis Giligenting with the theme "Building a Progressive Village Community" where the main aim of implementing this KKN is to build the spirit of the community to care more about the surrounding environment and invite the community to care for each other about the environment surrounding. , related to this program, we involve the Galis Village Youth Organization community group who work together in carrying out this activity with the Galis Village community.